Myles Brand: Intecollegiate Athletics Within the Limits of the Academic Mission Alone - Lou Matz (Journal of Intercollegiate Sport, 2021)
During his NCAA presidency, Myles Brand led novel academic reforms that gained deserved national recognition, but his defense of the educational and academic value of IA should be equally acknowledged since this was, for Brand, the ultimate reason why universities should support intercollegiate athletics (IA) in the first place. In this article, I describe the development of Brand’s view of the educational value of IA that preceded his signature 2006 publication ‘The Role and Value of Intercollegiate Athletics in Universities.’ I then explain Brand’s Integrated View of IA in his 2006 article and focus on his key argumentative strategy: the analogy of the educational value of IA to the educational value of performing arts like music and dance. I contend that Brand did not bring his persuasive analogical argument to its full logical conclusions since IA should contribute to a new academic major in Sport Performance and some of the very character virtues that Brand identified as developed ideally by IA are now recognized as essential academic liberal learning outcomes. I conclude by raising some criticisms of Brand’s view based on the organizational framework and policies of IA that create difficulties for the full realization of its educational value. Nonetheless, at a momentous time in U.S. higher education when university priorities and budgets are under perhaps unprecedented scrutiny, Brand’s insistence that IA must be integrated with the academic mission is more relevant than ever.